2001
DOI: 10.1509/jppm.20.1.84.17283
|View full text |Cite
|
Sign up to set email alerts
|

Attributions and Conformity in Illicit Consumption: The Mediating Role of Group Attractiveness

Abstract: Although research has demonstrated an association between certain types of explanations for peer-group illicit consumption and self-reported intentions to consume drugs and alcohol in response to peer influence, the mechanisms underlying these relationships have not been well studied. The results of two studies support predictions that group attractiveness mediates the effects of attributions regarding peer-group illicit consumption on intentions to conform. Normative attributions for group substance abuse wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Negative peer influence affects addictive consumption and maladaptive social behaviors tied to corporate advertising and promotion, including smoking (Pechmann and Knight, 2002), drinking (Duncan, Duncan, and Strycker, 2006), and drinking and driving (Hartos, Eitel, and Simons-Morton, 2002). This linkage leads social marketers to launch ad campaigns, and develop community and school interventions targeting children and teens to resist negative peer influence for both smoking (Pechmann and Knight, 2002) and drinking (Rose, Bearden, and Teel, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Negative peer influence affects addictive consumption and maladaptive social behaviors tied to corporate advertising and promotion, including smoking (Pechmann and Knight, 2002), drinking (Duncan, Duncan, and Strycker, 2006), and drinking and driving (Hartos, Eitel, and Simons-Morton, 2002). This linkage leads social marketers to launch ad campaigns, and develop community and school interventions targeting children and teens to resist negative peer influence for both smoking (Pechmann and Knight, 2002) and drinking (Rose, Bearden, and Teel, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…By examining the influence of the cosmetic purchasing experience as a moderating variable, the influence of susceptibility to global consumer culture on emotional and behavioral commitment can be understood more systematically and clearly. After Asch's [126] conformity experiment, many studies have shown that consumers are influenced by others' choices when purchasing products and tend to agree with others' choices [51,127]. Ratner and Kahn [128] argued that when making decisions in front of others in a personal situation, they choose to be different from others in order to show off their creativity and subjectivity.…”
Section: Moderating Effect Of Purchasing Experiencementioning
confidence: 99%
“…In addition, studies indicate that drug use is associated with peer influence and group attractiveness. Indeed, the more attractive the individual perceives illicit drug consumption to be, the more likely they are to give in to peer pressure in each situation (Rose et al, 2001). Research shows today's youth see marijuana as safe, believing it is a plant with minimal harmful attributes, aiding in their justification of experimentation (Bojkovsky et al, 2017).…”
Section: Factors Contributing To Marijuana Consumption Among Young Pementioning
confidence: 99%